Impacts of Climate Change in Central African Republic - Serge K.G, Soulé Baoro; Shaoxian, Song; Maidou Herve, Edo Ekata Emmanuel; Igor, Tola Kogadou (Journal of Environmental Science and Engineering Technology, 2017)
The purpose of this paper is to provide an overview of the Climate Change (CC) in the Central African Republic (CAR). Many researches on strategies to fight CC and reduce Green House Gas (GHGs) emissions have been conducted. However, implementation poses a serious problem at different levels including political, economic and socio-environmental. CC is seen as one of the greatest challenges of the 21st century. The CAR, like other countries of the world, has ratified the Kyoto Protocol on 1st January 2008, which aims to reduce the GHGs emissions responsible for CC. Almost all sectors (Energy, Agriculture, Forest, Health, Transport, Economy...) are affected by CC. GHGs are abundant in the Earth’s atmosphere. In the absence of efficient meteorological equipment and stations to save accurate data, the CAR and even Africa in general is considered a "black hole" of climate information which must be used by the Intergovernmental Panel-evolution of Climate change (IPCC) to evaluate effects of CC on the continent. Despite its low level of GHGs emissions, the CAR reaffirms its adherence to the principle of collective responsibility. Pursuant to 1CP / 19 (Further advancing the Durban Platform) by these ambitious measures to meet this challenge. Thus, in the CAR, political, military and economic constraints are obstacles to the implementation of strategies to fight CC. Given its low level of development, 80% of rural population, forests and lands of the CAR are the most affected by CC; These impacts in all sectors are very difficult to assess due to the lack of reliable data, of its very weak economy and the multiple armed conflicts that do not make the collection and updating of data easy, almost half of the territory 14 prefectures on 16 have been occupied by armed groups.